2011
DOI: 10.1111/j.1740-0929.2011.00979.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of a bovine myeloid antimicrobial peptide (BMAP‐28) against methicillin‐susceptible and methicillin‐resistant Staphylococcus aureus

Abstract: A bovine myeloid antimicrobial peptide (BMAP-28) is a member of the cathelicidin family which is included in the innate immune system of mammals. Recently, there have been many studies about antimicrobial peptides. This study aims to clarify whether BMAP-28 has bactericidal activity against methicillin-resistant Staphylococcus aureus (MRSA) and compares its activity against methicillin-susceptible S. aureus (MSSA) and MRSA. We found that the peptide was effective in killing MRSA (minimal inhibitory concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 17 publications
(33 reference statements)
2
23
0
Order By: Relevance
“…In general, the peptides under study showed a comparable efficacy to conventional antibiotics on a molar basis and moreover proved effective against a methicillin-resistant clinical isolate of S. epidermidis (MRSE). This adds to previous reports on the efficacy of BMAPs and their derivatives, as well as of P19, on antibiotic-resistant Gram-positives, including MRSA [23,25,44,50]. Moreover, peptides prevented S. epidermidis biofilm formation at microbicidal concentrations, with an all-or-nothing effect overall, likely due to rapid killing of bacteria before their deposition/attachment to the surface of microplate wells.…”
Section: Discussionsupporting
confidence: 64%
“…In general, the peptides under study showed a comparable efficacy to conventional antibiotics on a molar basis and moreover proved effective against a methicillin-resistant clinical isolate of S. epidermidis (MRSE). This adds to previous reports on the efficacy of BMAPs and their derivatives, as well as of P19, on antibiotic-resistant Gram-positives, including MRSA [23,25,44,50]. Moreover, peptides prevented S. epidermidis biofilm formation at microbicidal concentrations, with an all-or-nothing effect overall, likely due to rapid killing of bacteria before their deposition/attachment to the surface of microplate wells.…”
Section: Discussionsupporting
confidence: 64%
“…The activity was as good or better than those of vancomycin and other published antimicrobial peptides. [14][15][16][17]19,20 Although, host cytotoxicity and instability in vivo are major limitations of antimicrobial peptides in their application as antimicrobial drugs, we have reported recently that IP lacked toxicity to mammalian and human cells such as fibroblasts, colon epithelial cells and erythrocytes, and built a stable structure unlike other antimicrobial peptides. 12 Thus, IP combines the most important three advantages for clinical setting, which are potent bactericidal activity, low toxicity and structural stability.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,14 Strains were stored in Trypto Soya (TS; Nissui, Tokyo, Japan) broth with 20% glycerol at − 80°C until use and maintained on TS agar.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…; Takagi et al . ). It is also known as one of the representatives of the α‐helical type of cathelicidins (Zanetti ).…”
Section: Introductionmentioning
confidence: 97%